Evaluation of hemodialysis vascular access involving multidisciplinary integration: Perspective from Latin America and Peru - Castillo Velarde, Edwin; Ruiz-Peñafiel, José A.; Alfaro Ita, Sheyla; Vachharajani, Tushar J. (Frontiers in Nephrology, 2023)
The perspective of vascular access care in patients with end-stage renal disease has migrated from nephrology-centered or vascular surgery-centered care to multidisciplinary-focused patient-centered care. This new perspective should not only be theoretical but also have practical utility. A non-multidisciplinary focus can contribute to the low prevalence of arteriovenous fistula (AVF) in the population. Latin America has multiple health systems and the coordination of vascular access is heterogeneous. In Peru, there is a high prevalence of central venous catheter use with its associated complications, such as stenosis, thrombosis, infection, and recurrent hospitalizations in the context of fragmented care. However, in the last few years, there has been an effort to integrate the communication between vascular surgery, interventional radiology, and nephrology to improve vascular access care. In this review, we analyze the availability of care, the intervention, and the future directions from the experience of both perspectives.